2013
DOI: 10.1262/jrd.2012-121
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Adjuvants on Autoimmune Responses Against Testicular Antigens in Mice

Abstract: Experimental autoimmune orchitis (EAO) is a model of immunologic male infertility and pathologically characterized by lymphocytic inflammation, which causes breakdown of the testicular immune privilege with spermatogenic disturbance. Generally, murine EAO is induced by immunization with testicular homogenate (TH) from the testes of donor mice + complete Freund's adjuvant (CFA) + Bordetella pertussigens (BP), and it has been considered that treatment with these two adjuvants is required to enhance the immune re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 36 publications
(36 reference statements)
2
10
0
Order By: Relevance
“…In these studies, autoimmune reaction was evoked only against the haploid cells [24,28]. Moreover, we have previously demonstrated that autoantibodies against both the haploid cells and Sertoli cells can be detected in the sera of mice after combined treatment with CFA and BP but not with testicular antigens [42], indicating that the adjuvants themselves potentiate the induction of testicular autoimmune reactions against not only autoimmunogenic antigens but also other testicular components. In the current study, in all treated groups, the detected autoantibodies were directed against the haploid cells, and not against the other testicular components.…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, autoimmune reaction was evoked only against the haploid cells [24,28]. Moreover, we have previously demonstrated that autoantibodies against both the haploid cells and Sertoli cells can be detected in the sera of mice after combined treatment with CFA and BP but not with testicular antigens [42], indicating that the adjuvants themselves potentiate the induction of testicular autoimmune reactions against not only autoimmunogenic antigens but also other testicular components. In the current study, in all treated groups, the detected autoantibodies were directed against the haploid cells, and not against the other testicular components.…”
Section: Discussionmentioning
confidence: 99%
“…The differences in the development, course and severity of EAO between classical and TGC-induced disease models point to a significant influence of microbial components present in adjuvants and B. pertussis on inflammatory responses in the testis and epididymis. The use of CFA and Bp bacteria, in combination with TH, to induce EAO evokes more severe autoimmune reactions compared to the TGC-induced disease ( Musha et al , 2013 ) ( Supplementary Table SI ). Adjuvants are generally employed to enhance the inflammatory response during induction of organ-specific autoimmunity, e.g.…”
Section: Animal Models Of Autoimmune-based Testicular Inflammationmentioning
confidence: 99%
“…Therefore, we cannot estimate whether the autoimmune effects following the application of testicular homogenate are actually organ-specific to testicles and epididymides, as has been described before, or whether other organs and tissues, like bones for example, are directly affected by the autoimmune reaction as well [33]. On the other hand previous investigations illustrated that the supplemental application of complete Freund's adjuvant (CFA) and Bordetella pertussis toxin, beside testicular homogenate, is mandatory to evoke severe EAO [34]. However, treatment with the adjuvants alone can also evoke autoimmune reactions against some testicular autoantigens despite the use of no testicular homogenate [34].…”
Section: Discussionmentioning
confidence: 96%